A Poem, on the joyful news of the Rev. Mr. Whitefield's visit to Boston : dedicated to all the true friends of such "an exemplary Christian, fine gentleman and accomplish'd orator, who has discover'd in some late sermons such a deep insight into human nature, which abounded with fine characters, curiously pourtray'd, and his great skill in moral penciling, which with his manner of life, he's justly gain'd this character ([publisher not identified], 1754)
October 1754 poem written on the visit of Rev. Mr. Whitefield, an evangelical leader, to Boston.